2023
DOI: 10.18240/ijo.2023.05.03
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of ferulic acid against ionizing radiation-induced oxidative damage in rat lens through activating Nrf2 signal pathway

Abstract: AIM: To examine the protection of ferulic acid (FA) against ionizing radiation (IR)-induced lens injury in rats, as well as the underlying mechanisms. METHODS: FA (50 mg/kg) was administered to rats for 4 consecutive days before they were given 10 Gy γ-radiation, as well as for 3 consecutive days afterward. Two weeks after radiation, the eye tissues were collected. Histological alterations were evaluated by hematoxylin-eosin staining. Enzyme linked immunosorbent assay (ELISA) was utilized to assess the activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
(49 reference statements)
0
0
0
Order By: Relevance
“…Our research found that ferulic acid could reverse the ESC-induced reduction in the expression of Nrf2 and HO-1 that was associated with improvement in the muscle tissue structure, as indicated in the stained micro-images. Ferulic acid enhances the translocation of Nrf2 into the nucleus to promote its antioxidant protective effects [ 22 ]. Many experimental disease models have shown that ferulic acid activates Nrf2 and HO-1, but no previous research has illustrated its effect on any cancer type.…”
Section: Discussionmentioning
confidence: 99%
“…Our research found that ferulic acid could reverse the ESC-induced reduction in the expression of Nrf2 and HO-1 that was associated with improvement in the muscle tissue structure, as indicated in the stained micro-images. Ferulic acid enhances the translocation of Nrf2 into the nucleus to promote its antioxidant protective effects [ 22 ]. Many experimental disease models have shown that ferulic acid activates Nrf2 and HO-1, but no previous research has illustrated its effect on any cancer type.…”
Section: Discussionmentioning
confidence: 99%